2014
DOI: 10.3390/ph7060695
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis, Molecular Structure and Solid State Simulation of the Antiviral Drug Acyclovir (Zovirax) Using Density Functional Theory Methods

Abstract: The five tautomers of the drug acyclovir (ACV) were determined and optimised at the MP2 and B3LYP quantum chemical levels of theory. The stability of the tautomers was correlated with different parameters. On the most stable tautomer N1 was carried out a comprehensive conformational analysis, and the whole conformational parameters (R, β, Φ, φ1, φ2, φ3, φ4, φ5) were studied as well as the NBO Natural atomic charges. The calculations were carried out with full relaxation of all geometrical parameters. The searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Conformational data are usually obtained in solution by nuclear magnetic resonance (NMR) [ 12,13 ] and quantum chemical calculations [ 14,15 ] and in the solid‐state by NMR, [ 16,17 ] crystallography, [ 18,19 ] and again by quantum calculations. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational data are usually obtained in solution by nuclear magnetic resonance (NMR) [ 12,13 ] and quantum chemical calculations [ 14,15 ] and in the solid‐state by NMR, [ 16,17 ] crystallography, [ 18,19 ] and again by quantum calculations. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Conformational data are usually obtained in solution by nuclear magnetic resonance (NMR) [12,13] and quantum chemical calculations [14,15] and in the solidstate by NMR, [16,17] crystallography, [18,19] and again by quantum calculations. [20,21] In our previous paper, [1] the NMR data of these compounds were determined in solution and reported in the experimental section without comments. We elected to pursue a more detailed discussion of compounds previously reported [1] with the following differences:…”
mentioning
confidence: 99%
“…In addition, the triphosphorylated Acyclovir is recognized and incorporated 100 fold more efficiently by the viral DNA polymerase as compared to the cellular polymerase (King, 1988; Reardon and Spector, 1989). It has also been shown that Acyclovir’s inherent flexibility allows for optimized interactions in target enzyme binding sites (Alvarez-Ros and Palafox, 2014; Tuttle and Krenitsky, 1984; Wesołowski et al, 1987).…”
Section: Modifications To the Sugar Scaffoldmentioning
confidence: 99%
“…The Hyperquad Simulation and Speciation (HySS) was used to analyse zwitterion features of ACV to obtain the optimal conditions with the required flexibility for conjugation (Fig. 1b) 19,20 . Synthesized GNPs surface was capped with polybasic citrate (Fig.…”
Section: Design Synthesis and Characterization Of The Theranostic Gold Nanosystemsmentioning
confidence: 99%